RING OF SECURITY REVIEW ON THE VITAL OBJECTS OF THE ELECTRICITY SUBFIELD - Nurul Farida; Muhamad Syauqillah (Sean Institute, 2022)
Radicalism and extremism is a real threat to the Indonesian. The phenomenon of terrorism that has occurred in Indonesia does not necessarily occur but is a slow phenomenon and is preceded by stages of intolerance and radicalism and results in acts of terror in society. One of the goals of this group is to create chaos in society. They carry out attacks on vital objects. Therefore, the vital object security system is important. This paper discusses reviewing of security systems with the ring of security concept in a critical infrastructure in the electricity sub-sector. This paper aims is to find out how the security system is in this vital object and analyze its weaknesses so that recommendations are obtained as suggestions and input in the security system.